2021
DOI: 10.1371/journal.pone.0245749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese wolfberry and Astragalus extract on the antioxidant capacity of Tibetan pig liver

Abstract: The objective of this study is to determine the effect of Chinese wolfberry (Lycium barbarum) and Astragalus (Astragalus membranaceus) extract (WAE) on the antioxidant capacity of Tibetan pig liver, and discussed the regulatory effect of WAE on the liver antioxidant mechanism. Twelve healthy 120-day-old Tibetan black pigs (35±2 kg) were divided randomly into two groups. The WAE group was fed a basal diet supplemented with 1% WAE for 90 days. The control group was fed the same diet, but without the WAE. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Gum tragacanth ( Astragalus gossypinus ) is a polysaccharide extracted from the A. gossypinus stem. The gum tragacanth is a source of several active components such as glycosides, alkaloids, amino acids, flavonoids, trace minerals, saponins, and sugars (Hao et al, 2021 ). The beneficial effects of Astragalus root ( Radix astragali ) polysaccharides on liver protection, neuroprotection, oxidative stress, immunity, and inflammation have been confirmed (Jiang et al, 2010 ; Tiippana et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gum tragacanth ( Astragalus gossypinus ) is a polysaccharide extracted from the A. gossypinus stem. The gum tragacanth is a source of several active components such as glycosides, alkaloids, amino acids, flavonoids, trace minerals, saponins, and sugars (Hao et al, 2021 ). The beneficial effects of Astragalus root ( Radix astragali ) polysaccharides on liver protection, neuroprotection, oxidative stress, immunity, and inflammation have been confirmed (Jiang et al, 2010 ; Tiippana et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…SOD 1 and SOD 2 , such as Cu–Zn SOD and Mn SOD, are located in the cytoplasm and mitochondria ( 35 , 36 ). Chinese wolfberry and Astragalus extract (1%) notably improved the activities of SOD 1 , T-AOC, and CAT, and decreased MDA in Tibetan pig livers, and promoted the expression levels of hepatic antioxidant genes (e.g., CAT and SOD 1 ); this indicates that the extracts mechanism of regulating antioxidation is the signaling pathway of peroxisome antioxidant-oxidant stress in Tibetan pig livers ( 37 ). Another study investigated the effect of a plateau condition on oxidation in Tibetan pigs and Duroc × Landrace × Yorkshire (DLY) pigs, and found that Tibetan pigs exhibited higher SOD, GSH-Px, and T-AOC levels, but lower MDA levels in the liver and heart.…”
Section: Discussionmentioning
confidence: 98%
“…It is shown that SBE supplementation can potently attenuate diarrhea in weaning piglets and decrease inflammatory cytokine expression through inhibiting the NF-κB and P38 signaling pathways ( 123 ). Additionally, KEGG Pathway enrichment analysis by RNA sequencing shows that PI3K-Akt, AMPK, Rap1, and peroxisome signaling pathways are enriched in Tibetan pig liver after Chinese wolfberry ( Lycium barbarum ) and Astragalus ( Astragalus membranaceus ) extract treatment, and the plant extracts exert antioxidant and anti-stress ability ( 178 ). In vitro , OEO induces SOD1 and GSH expression through Nrf2 activation and alleviates hydrogen peroxide-induced oxidative damage in IPEC-J2 Cells ( 179 ).…”
Section: The Action Mechanisms Of Phytochemicalsmentioning
confidence: 99%